Impaired neutrophil directional chemotactic accuracy in chronic periodontitis patients. (8th January 2015) - Roberts, Helen M.; Ling, Martin R.; Insall, Robert; Kalna, Gabriela; Spengler, Julia; Grant, Melissa M.; Chapple, Iain L.C.
Abstract Aim To investigate the chemotactic accuracy of peripheral blood neutrophils from patients with chronic periodontitis compared with matched healthy controls, before and after non‐surgical periodontal therapy. Material & Methods Neutrophils were isolated from patients and controls (n = 18) by density centrifugation. Using the Insall chamber and video microscopy, neutrophils were analysed for directional chemotaxis towards N‐formyl‐methionyl‐leucyl‐phenylalanine [fMLP (10 nM), or CXCL8 (200 ng/ml)]. Circular statistics were utilized for the analysis of cell movement. Results Prior to treatment, neutrophils from patients with chronic periodontitis had significantly reduced speed, velocity and chemotactic accuracy compared to healthy controls for both chemoattractants. Following periodontal treatment, patient neutrophils continued to display reduced speed in response to both chemoattractants. However, velocity and accuracy were normalized for the weak chemoattractant CXCL8 while they remained significantly reduced for fMLP. Conclusions Chronic periodontitis is associated with reduced neutrophil chemotaxis, and this is only partially restored by successful treatment. Dysfunctional neutrophil chemotaxis may predispose patients with periodontitis to their disease by increasing tissue transit times, thus exacerbating neutrophil‐mediated collateral host tissue damage.